The Utilization of Noni leaf Silage ( Morinda citrifolia L.) with Marine Yeast Inoculant in Feed of Tambaqui (Colossoma macropomum) - Rambe, Rudy Hartawan; Suharman, Indra; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this research was to know the using effect of noni leaf silage on food efficiency and growth tambaqui (Colossoma macropomum) using the experimental method, completelly randomized design with one factor, five treatments and three replication which had different level comparison of soy bean meal and noni leaf silaged meal, spesifically P1 (100% TK:0%DM), P2 (90% TK:10%DM), P3 (80% TK:20%DM), P4 (70% TK:30%DM), dan P5 (60% TK:40%DM). The result indicated that feed with addition noni leaf silage meal on 10, 20, 30, and 40% were significant effect (P<0.05) on digestibility of feed, feed efficiency, protein retention and specific growth rate of tambaqui (Colossoma macropomum). The best treatment is obtained on P2 addition noni leaf silage as much as 20 % with average specific growth rate of 3.35 % /day and feed efficiency of 36.23 %. Key word : Noni leaf, silage, Tambaqui